The Molecular Mechanism of Scutellaria baicalensis Georgi Stems and Leaves Flavonoids in Promoting Neurogenesis and Improving Memory Impairment by the PI3K-AKT-CREB Signaling Pathway in Rats - Liu, Qian-Qian; Ding, Sheng-Kai; Zhang, Hui; Shang, Ya-Zhen (Combinatorial Chemistry & High Throughput Screening, 2022)
Aim: The aim of this study was to investigate the effect and molecular mechanism of Scutellaria baicalensis Georgi stems and leaves flavonoids (SSF) in promoting neurogenesis and improving memory impairment induced by the PI3K-AKT-CREB signaling pathway. Methods: Alzheimer's disease (AD) was induced in the male Wistar rats by intracerebroventricular injection of amyloid beta peptide 25-35 (Aβ25-35) in combination with aluminum trichloride (AlCl3) and recombinant human transforming growth factor-β1(RHTGF-β1) (composited Aβ). The Morris water maze was used to screen the successful establishment of the memory impairment model of rats. The screened successful model rats were randomly divided into a model group and three groups of three different doses of the drug (SSF). Rats in the drug group were treated with 35, 70, and 140 mg/kg of SSF for 43 days. The Eight-arm maze was used to measure the spatial learning and memory abilities of the rat, including working memory errors (WME) and reference memory errors (RME). Immunohistochemistry was used to detect the expression of BrdU, an indicator of neuronal proliferation, in the hippocampal gyrus of rats. The mRNA and protein expressions of TRKB, PI3K, AKT, P-AKT, and IGF2 in the PI3K-AKT-CREB signaling pathway in the hippocampus and cerebral cortex of the rats were determined by quantitative real-time PCR (qPCR) and Western blotting methods. Results: Compared to the sham group, the spatial memory ability of rats with composited Aβ was decreased, the number of WME and RME (P < 0.01) was increased, the expression of BrdU protein (P < 0.01) in the hippocampal gyrus was reduced, the mRNA and protein expression levels of TRKB, AKT, and IGF2 (P < 0.01, P < 0.05) in the hippocampus and cerebral cortex were lowered, and the mRNA expression level of PI3K (P < 0.01) in the cerebral cortex and the protein expression level of PI3K (P < 0.01) in the hippocampus were augmented. However, compared to the model group, the three-doses of SSF improved memory disorder induced by composited Aβ, reduced the number of WME and RME, increased the expression of BrdU protein in the hippocampal gyrus, and differently regulated the mRNA and protein expressions in composited Aβ rats. Conclusion: SSF improved memory impairment and neurogenesis disorder induced by composited Aβ in rats by activating the PI3K-AKT-CREB signaling pathway and up-regulating the mRNA and protein expressions of TRKB, PI3K, AKT, CREB, and IGF2.
Keywords: neurogenesis